Fluoxetine elevates allopregnanolone in female rat brain but inhibits a steroid microsomal dehydrogenase rather than activating an aldo‐keto reductase. (24th November 2014) - Fry, J P; Li, K Y; Devall, A J; Cockcroft, S; Honour, J W; Lovick, T A
<x xml:space="preserve">Abstract</x> Background and Purpose Fluoxetine, a selective serotonin reuptake inhibitor, elevates brain concentrations of the neuroactive progesterone metabolite allopregnanolone, an effect suggested to underlie its use in the treatment of premenstrual dysphoria. One report showed fluoxetine to activate the aldo‐keto reductase (AKR) component of 3α‐hydroxysteroid dehydrogenase (3α‐HSD), which catalyses production of allopregnanolone from 5α‐dihydroprogesterone. However, this action was not observed by others. The present study sought to clarify the site of action for fluoxetine in elevating brain allopregnanolone. Experimental Approach Adult male rats and female rats in dioestrus were treated with fluoxetine and their brains assayed for allopregnanolone and its precursors, progesterone and 5α‐dihydroprogesterone. Subcellular fractions of rat brain were also used to investigate the actions of fluoxetine on 3α‐HSD activity in both the reductive direction, producing allopregnanolone from 5α‐dihydroprogesterone, and the reverse oxidative direction. Fluoxetine was also tested on these recombinant enzyme activities expressed in HEK cells. Key Results Short‐term treatment with fluoxetine increased brain allopregnanolone concentrations in female, but not male, rats. Enzyme assays on native rat brain fractions and on activities expressed in HEK cells showed fluoxetine did not affect the AKR producing allopregnanolone from 5α‐dihydroprogesterone but did inhibit the microsomal dehydrogenase oxidizing allopregnanolone to 5α‐dihydroprogesterone. Conclusions and Implications Fluoxetine elevated allopregnanolone in female rat brain by inhibiting its oxidation to 5α‐dihydroprogesterone by a microsomal dehydrogenase. This is a novel site of action for fluoxetine, with implications for the development of new agents and/or dosing regimens to raise brain allopregnanolone.